Health Needs and Health Problems among Children of Women Attending Postnatal Care in Jos North Local Government Area of Plateau State, Nigeria - Haruna, Elizabeth A.; Gorah, Kajang Y. (NIU Journal of Humanities, 2020)
This research was carried out to know the health needs and health problems among children of women attending postnatal care in Jos North local government area of Plateau State. The research was conducted using cross-sectional survey research method through structured questionnaire which was administered to two hundred and fifty-five (255) women in Jos North local governmental area of Plateau State who served as the respondents.  The data collected from the respondent was analyzed using simple frequency and percentage method. The results revealed among others that immunization is a health needs of children 222 (88%), malnutrition is a health problem among children 209 (83%), lack of vitamin A is factor influencing the health problem of children 200 (80%) and mothers thinks that children dietary and nutritional requirements should differ from adult 41 (56%). Based on some of these, findings the respondents have a very high knowledge on the health needs and health problem among children of women attending postnatal care.  Based on some of the findings it was recommended that food rich in protein and carbohydrate should be given to children so as to help them to replace worn out tissues and also provides energy and that proper nutrient should be designed for children different from that of adult. Health seminars should be organizesoas to educate mother on the importance of giving their children balanced diet. Keywords: Health Needs, Health Problems and Women Attending Postnatal Care